2009
DOI: 10.2320/matertrans.m2009061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of B and Cr on Mechanical Properties and Magnetostriction of Iron-Gallium Alloy

Abstract: Effects of B and Cr additions on magnetostriction and the mechanical properties of polycrystalline Fe 83 Ga 17 alloy were investigated. Small addition of B increased magnetostriction of Fe 83 Ga 17 alloy slightly, and improved the room temperature ductility and tensile strength significantly. The elongation and tensile strength of the (Fe 83 Ga 17 ) 99 B 1 alloy increased to 3.56% and 548 MPa compared with that of Fe 83 Ga 17 alloy respectively. The Cr addition was shown to improve the room temperature mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 16 publications
2
15
0
1
Order By: Relevance
“…Directional solidification can decrease the density of transversal grain boundary, which could work as a method for improving the mechanical property of these alloys. As reported in previous studies, 19,20) the tensile strength of the equiaxed-grained FeGa (1518 at%) alloy without preferred orientation was about 380³450 MPa at room temperature, and the fracture mode was intergranular fracture. It is considered that the tensile strength depends on the grain boundary bonding strength.…”
Section: Resultssupporting
confidence: 76%
“…Directional solidification can decrease the density of transversal grain boundary, which could work as a method for improving the mechanical property of these alloys. As reported in previous studies, 19,20) the tensile strength of the equiaxed-grained FeGa (1518 at%) alloy without preferred orientation was about 380³450 MPa at room temperature, and the fracture mode was intergranular fracture. It is considered that the tensile strength depends on the grain boundary bonding strength.…”
Section: Resultssupporting
confidence: 76%
“…6). Nonetheless, we will limit our analysis to octahedral interstitial to be consistent with the earlier experimental works (Gao et al, 2009), and the energy results reported in Table 1. It should be noted that the boron solutes for the case of octahedral sites are pushed further into the improper sites which lie along the close packed directions (hereafter, we refer these improper sites as the "xenohedral" sites, and will be discussed later).…”
Section: Atomistic Simulationssupporting
confidence: 78%
“…Pseudoelasticity is a consequence of reversible pseudotwinning, a form of twinning in ordered alloys, and reversible slip. Alloying of FeeGa crystals with boron has proven beneficial for improving the ductility and flow stress (Gao et al, 2009). In this paper, we explore the elevation in critical twinning stress in the D0 3 ordered Fe 3 Ga crystals with boron with atomisticemicromechanical treatments.…”
Section: Introductionmentioning
confidence: 99%
“…3a). But the Fe 2 B phase was not identified duo to low content [17]. A farthing of B could enter interstitially into the octahedral site as in pure ␣-Fe as discussed by Clark [12] and Huang [19].…”
Section: Effect Of Heat Treatment On Magnetostriction and Texture Of mentioning
confidence: 95%
“…The increase of grain boundaries area leaded to an increase of resistance to crack propagation. Therefore, B improved the ductility and strength of the Fe-Ga alloy [17]. Liu et al [18] have pointed out that the beneficial effect of Cr on ductility of the Fe 3 Al alloy was attributed to the easy cross-slip behavior of dislocations and solution softening.…”
Section: Effect Of B and Cr Additions On The Mechanical Property Of Fmentioning
confidence: 99%